Gold-Ruthenium Alloy Nanoparticles Modified Glassy Carbon Electrode as a Sensing Platform for the Trace Level Detection of Indol-3-Carbaldehyde. Issue 12 (18th August 2017) - Shah, Afzal; Mahmood, Ansar; Mehmood, Rashad; Rehman, Saif ur; Ozkan, Sibel Aysil; Shah, Aamir Hassan
Abstract : In the present work we have proposed a novel strategy for the detection of indol-3-carbaldehyde (I3C) using Au-Ru alloy nanoparticles (NPs) modified glassy carbon electrode. The work is focused on achieving the optimum conditions for getting robust signal of I3C over NPs modified electrode surface. The alloy NPs of Au-Ru were synthesized by polyols method and characterized by XRD and UV-visible spectroscopy. Cyclic, square wave and differential pulse voltammetry were used for investigating the performance of the designed sensor for the electroanalysis of I3C. The developed sensor showed nice voltammetric response in media of different pH and demonstrated remarkable electrocatalytic activity and anti-interference ability. A linear calibration curve for indol-3-carbaldehyde was obtained in the concentration range of 20–100 μM with a correlation coefficient of 0.99. The results revealed that 1.89 μM concentration of I3C can be reliably detected at Au-Ru modified glassy carbon electrode. Moreover, the designed sensor showed excellent analytical characteristics such as high selectivity, reproducibility, wide linearity range and lower limit of detection.